Metabolic adaptations to a high-fat diet in endurance cyclists - Goedecke, J. H.; Christie, C.; Wilson, G.; Dennis, S. C.; Noakes, T. D.; Hopkins, W. G.; Lambert, E. V. (Metabolism, 1999)
We examined the time course of metabolic adaptations to 15 days of a high-fat diet (HFD). Sixteen endurance-trained cyclists were assigned randomly to a control (CON) group, who consumed their habitual diet (30% +/- 8% mJ fat), or a HFD group, who consumed a high-fat isocaloric diet (69% +/- 1% mJ fat). At 5-day intervals, the subjects underwent an oral glucose tolerance test (OGTT); on the next day, they performed a 2.5-hour constant-load ride at 70% peak oxygen consumption (VO2peak), followed by a simulated 40-km cycling time-trial while ingesting a 10% 14C-glucose + 3.44% medium-chain triglyceride (MCT) emulsion at a rate of 600 mL/h. In the OGTT, plasma glucose concentrations at 30 minutes increased significantly after 5 days of the HFD and remained elevated at days 10 and 15 versus the levels measured prior to the HFD (P < .05). The activity of carnitine acyltransferase (CAT) in biopsies of the vastus lateralis muscle also increased from 0.45 to 0.54 micromol/g/min over days 0 to 10 of the HFD (P < .01) without any change in citrate synthase (CS) or 3-hydroxyacyl-coenzyme A dehydrogenase (3-HAD) activities. Changes in glucose tolerance and CAT activity were associated with a shift from carbohydrate (CHO) to fat oxidation during exercise (P < .001), which occurred within 5 to 10 days of the HFD. During the constant-load ride, the calculated oxidation of muscle glycogen was reduced from 1.5 to 1.0 g/min (P < .001) after 15 days of the HFD. Ingestion of a HFD for as little as 5 to 10 days significantly altered substrate utilization during submaximal exercise but did not attenuate the 40-km time-trial performance.